2004
DOI: 10.1016/j.physa.2004.05.031
|View full text |Cite
|
Sign up to set email alerts
|

The spread of infectious disease on complex networks with household-structure

Abstract: In this paper we study the household-structure SIS epidemic spreading on general complex networks. The household structure gives us the way to distinguish inner and the outer infection rate. Unlike household-structure models on homogenous networks, such as regular and random networks, here we consider heterogeneous networks with arbitrary degree distribution p(k). First we introduce the epidemic model. Then rate equations under mean field appropriation and computer simulations are used here to analyze our mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…I. In many models, diverging second moments of the degree distribution extinguishes the epidemic thresholds, as reported previously for the percolation [2,9,10,33], the contact process [16,36,37], the SIR model [4,29,30,32], the SIRS model [25], and the household moodel [26]. On scale-free networks, which underly sexually transmitted diseases and computer viruses (see Sec.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…I. In many models, diverging second moments of the degree distribution extinguishes the epidemic thresholds, as reported previously for the percolation [2,9,10,33], the contact process [16,36,37], the SIR model [4,29,30,32], the SIRS model [25], and the household moodel [26]. On scale-free networks, which underly sexually transmitted diseases and computer viruses (see Sec.…”
Section: Discussionsupporting
confidence: 55%
“…1(C) [25]. They also studied the household model, in which each vertex has a graded state corresponding to the number of patients in a household [26]. They showed that the epidemic thresholds are proportional to k / k 2 also in these models.…”
Section: Introductionmentioning
confidence: 99%
“…But this network has been found to be disassortative mixing, which is a typical characteristic of nonsocial networks. Another shortcoming of most previous generative models is that they do not consider the local structures, especially the household structure, which has been found to be an important constituent for social contact networks, and has critical impact on the epidemic spreading process [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…There are some network models that consider with demographics. For instance, Liu et al (2004) introduced an epidemic model with birth and death in networks, however, they also assumed that the size of the network was constant, and each site on the network was occupied by at most one individual and was otherwise empty. Jin et al (2014) initially proposed an epidemic model on networks with demographics and conducted various dynamic analyzes based on this model.…”
Section: Introductionmentioning
confidence: 99%